Classification of the agricultural potential of Couto de Magalhães de Minas using geoprocessing tools (Revista Espinhaço, 2025)
The advancement of geotechnologies and the increased availability of open-access geospatial data contribute significantly to urban and rural planning by enabling the formulation of more precise public policies aimed at fostering municipal and regional socioeconomic development. Within this context, the present study aimed to model the agricultural potential of the municipality of Couto de Magalhães de Minas, located in the Alto Jequitinhonha region. Initially, a survey of publicly available geospatial datasets was conducted to select and acquire appropriate vector and raster data suitable for integration into the proposed modeling framework. Using geoprocessing techniques and tools within QGIS 3.16.4 Hannover with GRASS GIS 7.8.5, thematic maps were generated for soil classes, topographic relief, soil erodibility, hypsometry, vegetation and land use/land cover. These thematic layers were integrated using the Analytical Hierarchy Process (AHP) and Weighted Linear Combination (WLC) methods to derive the final agricultural potential map of the municipality. The resulting model indicated that 49% of the municipality’s territory exhibits low agricultural potential, 21% is classified as unsuitable for agricultural development, while areas of high and moderate potential represent 15% each.
Keywords: mapping; family farming; soils; Jequitinhonha; QGIS